Rare and uncommon diseases of the hip: arthroscopic treatment - Christian Carulli; Alberto Schiavo; Alberto Rigon; Wondi De Marchi; Matteo Innocenti; Luigi Meccariello; Massimo Innocenti (Medicinski glasnik, 2020)
Aim: Uncommon and rare hip diseases are sources of pain and functional limitation particularly in young patients. Some of these conditions may be nowadays treated by arthroscopy due to the expertise and technical tips that high-volume hip arthroscopies have achieved during the last decades ensuring a wider range of indications for such a procedure. The aim of this study was to evaluate clinical results of arthroscopy in treating uncommon or rare diseases of the hip at a single Institution. Methods: Thirteen patients affected by several types of diseases were treated by a hip arthroscopy and retrospectively evaluated. All patients were operated by the same surgeon, instrumentation and technique, but postoperative rehabilitative protocol was tailored on each patient and his disease. Each patient underwent a specific imaging, consisting of dedicated x-rays and arthro-MRI. Modified Harris Hip score (mHHS) and Non-Arthritic Hip score (NAHS) were used before and after surgery to clinically assess the outcome. Results: All patients reported satisfaction, pain relief, and a good functional recovery at the latest follow-up visit. Only one patient affected by chondromatosis reported a recurrence of synovitis and needed a further arthroscopy 25 months after the index operation. No complications were reported at the latest follow-up. The NAHS and mHHS showed good improvements and all patients referred high satisfaction. Conclusion: Hip arthroscopy performed by expert and high-volume surgeons may ensure good results in patients affected by uncommon and rare hip diseases.
Keywords: arthroscopy; hip; hip joint/pathology; hip joint/surgery